Age and sex-specific associations of carotid pulsatility with small vessel disease burden in transient ischemic attack and ischemic stroke - Lau, K; Pego, P; Mazzucco, S; Li, L; Howard, D; Küker, W; Rothwell, P (SAGE Publications, 2018)
Background and Purpose Although large artery stiffness has been implicated in the pathogenesis of cerebral small vessel disease (SVD), whether carotid pulsatility, a convenient surrogate marker of arterial stiffness, is similarly associated with global burden of SVD is unknown. Methods We studied consecutive patients with TIA or non-disabling ischaemic stroke from the Oxford Vascular Study who had a brain MRI and carotid duplex ultrasound during 2002-2014. We determined clinical correlates of common carotid (CCA) and internal carotid artery (ICA) pulsatility index (PI) and their associations with the Total SVD Score on MRI, stratified by age (median=72). Results In 587 patients, CCA and ICA-PI were both independently associated with age, diabetes and premorbid mean pulse pressure after adjustment for age, sex and cardiovascular risk factors (all p<0.05). ICA-PI was strongly associated with SVD markers and burden, particularly lacunes, in patients aged<70 (age and sex-adjusted OR of top vs. bottom PI quartile: 5.35, 1.95-14.70, p=0.001; increasing SVD Score:2.30, 1.01-5.25, p=0.048), but not in patients aged≥70 (p>0.05). No associations between CCA-PI with SVD Score were noted at any age. In 94 consecutive patients who also received transcranial Doppler ultrasound, strong associations between middle cerebral artery (MCA)-PI and an increasing SVD Score was noted (unadjusted OR - MCA:4.26,1.45-12.55, p=0.009; ICA:2.37,0.81-6.87, p=0.11; CCA:1.33,0.45-3.96, p=0.61). Conclusions ICA and MCA-PI are associated with global SVD burden, especially in individuals aged<70 and may be causally related.